2019
DOI: 10.3390/foods8100496
|View full text |Cite
|
Sign up to set email alerts
|

Rice-Buckwheat Gluten-Free Pasta: Effect of Processing Parameters on Quality Characteristics and Optimization of Extrusion-Cooking Process

Abstract: A new type of gluten-free pasta has been developed based on a rice-buckwheat mixture. The aim of the study was to investigate the effect of process parameters of moisture content (30, 33, and 36%), barrel temperature (80, 100, and 120 °C), and screw speed (60, 80, and 100 rpm) on cooking and textural properties of rice-buckwheat pasta produced by a single-screw extrusion-cooker. The process uses response surface methodology based on a Box-Behnken experimental design. Results showed that with regard to this ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
5
20
0
Order By: Relevance
“…In contrast, at higher screw speed, the hydrated pasta firmness increased as the moisture content increased (Figure 2b). Similar observations have been reported for other gluten-free pastas [3,20,21,38,39]. At higher moisture content and lower screw speed, shearing stresses are low, and therefore the degree of starch gelatinization decreases, resulting in poor strength and lower firmness (the opposite is true for lower moisture content and higher screw speed) [40].…”
Section: Effect Of Extrusion-cooking Parameters On the Textural Properties Of Rice Pastasupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast, at higher screw speed, the hydrated pasta firmness increased as the moisture content increased (Figure 2b). Similar observations have been reported for other gluten-free pastas [3,20,21,38,39]. At higher moisture content and lower screw speed, shearing stresses are low, and therefore the degree of starch gelatinization decreases, resulting in poor strength and lower firmness (the opposite is true for lower moisture content and higher screw speed) [40].…”
Section: Effect Of Extrusion-cooking Parameters On the Textural Properties Of Rice Pastasupporting
confidence: 77%
“…We found that the hardness of the dry rice pasta during the cutting test increased when the screw speed increased (r = 0.65) (Figure 2a). Bouasla and Wójtowicz [38] and Wójtowicz [39] reported similar findings for gluten-free pasta made from rice-buckwheat flour and buckwheat flour, respectively. The hardness of rice pasta also increased as feed moisture increased from 28% to 30% and then decreased when feed moisture increased to 32%.…”
Section: Effect Of Extrusion-cooking Parameters On the Textural Properties Of Rice Pastamentioning
confidence: 54%
“…The prepared mixtures were extruded by way of a modified single-screw extruder TS-45 type (ZMCh Metalchem, Gliwice, Poland) with installed power of 10 kW to obtain the flat form of snack pellets. The extrusion was carried out using a L/D = 18 plasticizing unit with an intensive glycol cooling system in the last barrel section [25]. The temperature range in individual extruder sections was as follows: dosing section 80-85 • C, plasticizing section 90-105 • C, cooling section 50-65 • C and forming die 60-75 • C. The pellets were shaped to a flat strip form using a 30 mm × 0.4 mm die head and were cut to the final dimensions of about 30 mm × 30 mm.…”
Section: Raw Materials and Processingmentioning
confidence: 99%
“…Increased rice production, leading to generation of large quantities of broken rice in some tropical countries including Nigeria, highlights the opportunities for the production of rice pasta. Rice flour has been used as major ingredient for pasta production ( Lai, 2001 ; Sandhu and Kaur, 2010 ; Ahmed et al., 2016 ; Ribeiro et al., 2018 ; Bouasla and Wójtowicz, 2019 ).…”
Section: Introductionmentioning
confidence: 99%